EFFICACY OF TRADI IN TEACHING HOLISTIC HEALTH IN GRADE 11 HUMSS STUDENTS AT BESTLINK COLLEGE OF THE PHILIPPINES (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
In this modern era, the combination of traditional and digital teaching methods has transformed the effectiveness and efficiency of education, providing learners with essential tools for achieving quality learning. These methods serve as core strategies in enhancing the teaching and learning process. However, while education continues to evolve, addressing mental health remains a significant challenge. According to a 2019 study by Sweeney et al., the stigma surrounding mental health can prevent individuals from seeking the support they need, making it more difficult to attain overall well-being. Implementing holistic approaches—which emphasize the connection between mental and physical health—can be especially challenging when working with individuals who have experienced trauma or long-term mental health issues. Due to its complexity, mental health is often regarded as one of the most difficult aspects to address within a holistic framework. The researchers utilized a purposive sampling technique to select participants, in line with the parameters of a quasi-experimental research design grounded in a quantitative methodology. This study specifically aimed to assess the effectiveness of the TraDi teaching approach in fostering holistic health among fifty (50) Grade 11 senior high school students at Bestlink College of the Philippines. The findings demonstrated that the implementation of the TraDi (Traditional-Digital) instructional material was highly effective in enhancing the holistic development of Grade 11 students. Prior to the intervention, students achieved a mean pre-test score of 12.50. Following the use of the TraDi instructional material, the mean post-test score increased substantially to 22.20. This notable improvement highlights the instructional material’s positive impact on students’ overall performance. The results provide strong evidence that the TraDi approach significantly contributes to fostering a more comprehensive and effective learning experience. The cultivation of self-care, self-awareness, self-efficacy, and self-directed learning empowers individuals with a greater sense of control over their overall well-being, resulting in improved adherence to healthy behaviors and enhanced learning capacity. The implementation of the TraDi (Traditional-Digital) teaching approach further supported this development by fostering students’ awareness of the interconnected nature of human health, encompassing mental, physical, emotional, social, environmental, and spiritual dimensions. This holistic perspective not only enriched their educational experience but also promoted a more comprehensive understanding of personal well-being.
Keywords: tradi approach; holistic learning; self-care; self-awareness; self-efficacy; self-directed learning; student well-being; interconnected health; traditional-digital instruction; health education